Hakikat dan Eksistensi Peradilan Adat di Sulawesi Selatan - Buana, Andika Prawira; APHA, Journal Manager (Asosiasi Pengajar Hukum Adat (APHA) Indonesia, Fakultas Hukum Universitas Trisakti - Jakarta Barat, Indonesia, 2018)
The adat justice is an institution that has a function to examine and try a case for the realization of a sense of justice in society. The adat justice has the main objective to restore social balance in society so that there is no revenge due to the dispute. The main objective which is the focus of this research is how is the essence and existence of adat justice in South Sulawesi. This study uses empirical legal research methods. The results of this study illustrate that traditional justice has always existed in South Sulawesi which is stated in the concept of ‘pangngaderreng’ with the term 'bicara' and is the only institution in solving cases that occur in the community. After the independence of the judiciary is no longer recognized with the reason for the realization of a unity of power in which the judiciary is subject to State legal authority.